2003
DOI: 10.1111/j.0303-6979.2004.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor oral health is associated with coronary heart disease and elevated systemic inflammatory and haemostatic factors

Abstract: The present study suggests an association between poor oral status and CHD, and provides evidence that inflammatory and haemostatic factors could play an important role in this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 41 publications
3
103
0
5
Order By: Relevance
“…results as this study that subjects who have periodontal infections, such as gingivitis and periodontitis have higher levels of CRP than subjects without gingivitis and periodontitis [11][12][13] respectively, supporting the hypothesis that these oral infections increase CRP levels, moreover, some intervention studies have also support this study results that periodontal treatment reduces CRP levels. 10,14 The results of the study showed that there was a 35% decrease in CRP level in periodontitis patients that used Dental Air Force home dental cleaning system without undergoing phase 1 (complete scaling and root planing) therapy.…”
Section: Ijedssupporting
confidence: 83%
“…results as this study that subjects who have periodontal infections, such as gingivitis and periodontitis have higher levels of CRP than subjects without gingivitis and periodontitis [11][12][13] respectively, supporting the hypothesis that these oral infections increase CRP levels, moreover, some intervention studies have also support this study results that periodontal treatment reduces CRP levels. 10,14 The results of the study showed that there was a 35% decrease in CRP level in periodontitis patients that used Dental Air Force home dental cleaning system without undergoing phase 1 (complete scaling and root planing) therapy.…”
Section: Ijedssupporting
confidence: 83%
“…It has been observed that the serum levels of anti-oxLDL were significantly higher in CVD patients with greater severity of periodontal disease (Montebugnoli et al 2004(Montebugnoli et al , 2005, and Monteiro (Monteiro et al 2009) demonstrated that periodontitis patients' sera contain higher concentrations of antibodies against oxidized LDL than healthy controls. It has been proposed that oxLDL that is opsonized by antibodies such as anti-PC, anti-oxLDL and anti-CL, could promote systemic inflammation through interactions with DC's, which produce IL-12 and IL-18 leading to IFN-c production.…”
Section: Other Antibodiesmentioning
confidence: 99%
“…Oral health has not been seen as a priority in this group, although poor dental hygiene impacts on quality of life, affecting everyday functioning such as eating, comfort, appearance, social acceptance and self esteem, it is unlikely to be fatal (Cormac 1999). Poor oral health, however, has been linked to coronary heart disease (Montebugnoli 2004) and oral health is an important part of overall physical health. Many drugs routinely prescribed to those with serious mental illness lead to changes in physiology, some of which can be dangerous; the recognition of this has largely driven the monitoring of physical health symptoms in this client group.…”
Section: B a C K G R O U N D Description Of The Conditionmentioning
confidence: 99%